إشكالية التنمية وإنعكاساتها على الامن والاستقرار في إفريقيا - غراب محمد رفيق (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
ملخص تندرج الدراسة ضمن المواضيع المرتبطة بمعضلة الفشل التنموي الذي تعاني منه إفريقيا منذ الاستقلال، رغم المحاولات المتكررة للنهوض باقتصادات دولها، هذا الفشل له انعكاسات سلبية أثرت على التنمية. تعالت اصوات حول أسباب هذا الفشل علما أن البلدان الإفريقية تلقت قروضا من المؤسسات المالية الدولية مرفوقة بمشروطيه وقيود تحد من حرية الأنظمة في التصرف. لذا كان التركيز على أهم المقاربات التي تقبل الإسقاط على الواقع الإفريقي، فإفريقيا تزخر بموارد طبيعية مازالت محل اطماع القوى الاقتصادية العالمية، ولها من الكفاءات ما يؤهلها لاحتلال مراتب متقدمة على المستوى العالمي. إن فشل التنمية يهدد الأمن والاستقرار في هذه البلدان ولهذا دأبت الدراسة على محاولة استجلاء اهم الاسباب الرئيسية التي كانت وراء هذا الفشل واهم انعكاساتها على الامن و الاستقرار وصولا الى الاستنتاجات التي تلخص أهم النتائج التي توصلت لها الدراسة . Abstract: The study falls within the topics related to the dilemma of development failure suffered by African countries since independence, despite repeated attempts to advance the economies of these countries, this failure accompanied by negative repercussions that affected the development process. Given that African countries received loans from international financial institutions by conditionalities and restrictions that limit the action of the regimes. Therefore, the focus was on the most important approaches that accept the projection of the African reality, Africa is rich in natural resources that are still subject to the ambitions of global economic powers, and it has the human competencies that qualify it to occupy advanced ranks at the global level. The failure of development threatens security and stability in these countries. That is why the study has been trying to clarify the main reasons behind this failure and its most important repercussions on security, and stability arriving at the conclusions that summarize the most important findings of the study.